(untitled) (Scientific journal of the Fergana State University, 2026)
This article scientifically analyzes the relevance of forming and developing the professional skills of future teachers, their role in ensuring readiness for modern pedagogical activity, and their contribution to improving the quality of education. In addition, the factors influencing the development of professional skills, effective methods, and practical approaches are presented.